2010
DOI: 10.1086/657121
|View full text |Cite
|
Sign up to set email alerts
|

Pandemic Influenza A (H1N1) Outbreak among 15 School‐Aged HIV‐1–Infected Children

Abstract: Patients infected with human immunodeficiency virus type 1 (HIV-1) are considered to be at increased risk for 2009 H1N1 influenza-related complications. We performed an observational study after an outbreak of 2009 H1N1 influenza virus infection among a group of 15 HIV-1-infected school-aged children in Germany in October 2009. Clinical course, kinetics of viral shedding, and antibody response among children with CD4 cell counts >350 cells/μL and 2009 H1N1 influenza virus coinfection did not appear to differ f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
15
0

Year Published

2011
2011
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 17 publications
5
15
0
Order By: Relevance
“…In an outbreak of 2009 H1N1 influenza virus infection in Germany involving 15 HIV-infected schoolchildren receiving cART, the clinical course in HIV-infected children was similar to that in HIV-uninfected children. 15 A case series of 13 HIV-infected children with 2009 H1N1 in Barcelona also reported outcomes similar to those in HIV-uninfected groups. 16 In both reports, half of the children were aged <13 years, had CD4 counts >500 cells/mm 3 , and very low or undetectable HIV viral loads.…”
Section: Influenza (Last Updated November 6 2013; Last Reviewed Novementioning
confidence: 71%
See 3 more Smart Citations
“…In an outbreak of 2009 H1N1 influenza virus infection in Germany involving 15 HIV-infected schoolchildren receiving cART, the clinical course in HIV-infected children was similar to that in HIV-uninfected children. 15 A case series of 13 HIV-infected children with 2009 H1N1 in Barcelona also reported outcomes similar to those in HIV-uninfected groups. 16 In both reports, half of the children were aged <13 years, had CD4 counts >500 cells/mm 3 , and very low or undetectable HIV viral loads.…”
Section: Influenza (Last Updated November 6 2013; Last Reviewed Novementioning
confidence: 71%
“…1517 Loss of appetite was more common in HIV-infected patients than in HIV-uninfected patients in one study. 18 In a prospective cohort study conducted in South Africa from 1997 to 1999, prior to cART availability, hospitalized HIV-infected children with laboratory-confirmed influenza had more radiographic evidence of alveolar consolidation when compared with HIV-uninfected children.…”
Section: Influenza (Last Updated November 6 2013; Last Reviewed Novementioning
confidence: 95%
See 2 more Smart Citations
“…Although our study did not determine which fatalities had acquired immunodeficiency syndrome or were on antiretroviral therapy, we found a higher prevalence of influenza A H1N1pdm co-infection among HIV positive fatalities when compared to the general population. Such data are important because early reports suggested that HIV-infected individuals might experience more severe complications from influenza A H1N1pdm infection [20], [24], [25], [26], a finding not confirmed in later studies [27], [28], [29].…”
Section: Discussionmentioning
confidence: 93%